Micronutrient inadequacy among lactating mothers in rural areas of North Mecha District, Amhara Region, Ethiopia - Menber, Yonatan; Gashaw, Selamawit; Belachew, Tefera; Fentahun, Netsanet (Frontiers in Nutrition, 2024)
Background: Lactating women are frequently at risk for nutritional deficiencies due to the physiological requirements of lactation. Throughout the world, a significant number of lactating women have micronutrient intake inadequacy. Evidence on micronutrient intake during lactation is limited in rural Ethiopia. Therefore, this study aimed to determine micronutrient intake inadequacy and associated factors among lactating women. Methods and materials: A community-based cross-sectional study was conducted from February 1 to 18, 2023, among lactating mothers. in rural areas of North Mecha District, Northwest Ethiopia. A multistage sampling technique was used to select 449 study participants. An interviewer-administered questioner was employed to collect data. The NutriSurvey 2007 software and Ethiopia, Tanzania and Kenya food composition tables were used to calculate nutrient values for the selected 12 micronutrients. For the remainder of the analysis, SPSS version 25 was employed. The Nutrient Adequacy Ratio and Mean Adequacy Ratio were calculated to evaluate the nutrient intakes. A multivariable binary logistic regression analysis was conducted to determine the factors contributing to the overall micronutrient intake inadequacy. Result: The overall prevalence of micronutrient intake inadequacy was 72.3%. The odds of micronutrient intake inadequacy were 2.5 times higher among lactating women aged 18–25 years old as compared to women in the age group 36–50 years old. Women with educational status of unable to read and write and able to read and write were 3.5 and 3.6 times more likely to have micronutrient intake inadequacy than women with secondary school completed and above educational status, respectively. Women whose partners were other than farmers in occupation were 3.3 times more likely to have micronutrient intake inadequacy compared to women whose partners were farmers. The likelihood of micronutrient intake inadequacy was 1.8 times higher among women from food-insecure households than their counterparts. The odds of micronutrient intake inadequacy were 1.8 times higher among women who had a nutrition-related unfavorable attitude than those who had a favorable attitude. Conclusion: The results showed that prevalence of micronutrient intake inadequacy among lactating women was high. Women's age, women's education, partners' occupation, household food security, and nutrition-related attitude were significantly associated with micronutrient inadequacy.